Yoga Ocular Exercises to Maintain Eye Health During Work and Distance Learning in the New Normal Era - Ayunda Puteri Rizanti (Universitas Muhammadiyah Surakarta, 2021)
The COVID-19 outbreak is a challenge for the world of work and education to change all activities from face-to-face system into remote system with internet and technology-based online system. These online activities lead to increased exposure from digital screen such as computers and mobile phones in the society. Viewing a computer or digital screen often makes our eyes work harder, this high visual demands of digital screen display makes many people susceptible to the development of vision-related symptoms. This article aims to determine the effect of yoga ocular exercises on eye fatigue and increase eye health The method we used was a literature study that focused on yoga ocular interventions in overcoming eye fatigue with databases in the form of PubMed, Willey, Proquest and, Google Scholar published in 2015-2020. Through a review of 8 selected articles, the results showed that yoga ocular practice provides benefits in the form of reduce eye fatigue, relax the mind, prevent asthenopia symptoms, improve binocular vision function by increasing the efficiency of eye motility muscles, and also reduce the intraocular pressure in glaucoma patients. Through the review, it can be seen that yoga ocular practice can prevent vision problems and maintain eye health in the new normal era